Assessing The Mechanical Properties And Performance Of Biocomposite And Natural Fiber Based Bulletproof Vests - Nabilla, Dhawya Najma; Aritonang, Sovian; Muniarti, Riri (Rekayasa Material, Manufaktur dan Energi, 2024)
Within the munitions industry, there has been a notable emphasis on the development of cost-effective, easily wearable, and biocompatible flak armor. The rising popularity of fiber-reinforced polymer biocomposite technology, particularly employing natural fibers, stems from its eco-friendliness and cost-effectiveness, which holds particular significance in today's defense sector. As firearm technology advances rapidly, it necessitates a concurrent focus on enhancing personal protective equipment, with bulletproof vests being a commonly utilized safeguard. These vests play a critical role in mitigating the impact of ballistic threats on individuals. This study is dedicated to the investigation of natural fiber biocomposite materials for their applicability in bulletproof vests, addressing their mechanical properties and suitability for such a vital protective role.